2023
DOI: 10.1099/mic.0.001409
|View full text |Cite
|
Sign up to set email alerts
|

Under conditions closely mimicking vaginal fluid, Lactobacillus jensenii strain 62B produces a bacteriocin-like inhibitory substance that targets and eliminates Gardnerella species

Stephany Navarro,
Habib Abla,
Jane A. Colmer-Hamood
et al.

Abstract: Within the vaginal ecosystem, lactobacilli and Gardnerella spp. likely interact and influence each other’s growth, yet the details of this interaction are not clearly defined. Using medium simulating vaginal fluid and a two-chamber co-culturing system to prevent cell-to-cell contact between the bacteria, we examined the possibility that Lactobacillus jensenii … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
(154 reference statements)
0
2
0
Order By: Relevance
“…Communities dominated by lactobacilli are frequently associated with 'health' or lack of symptoms [3,4]. Lactobacillus strains isolated from female urogenital samples have routinely exhibited antimicrobial properties [5][6][7][8][9][10][11], suggesting that they play a role in inhibiting or killing pathogens in the urinary tract and/or vagina. Studies of the healthy (asymptomatic) bladder microbiome have shown that it is frequently predominated by lactobacilli [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communities dominated by lactobacilli are frequently associated with 'health' or lack of symptoms [3,4]. Lactobacillus strains isolated from female urogenital samples have routinely exhibited antimicrobial properties [5][6][7][8][9][10][11], suggesting that they play a role in inhibiting or killing pathogens in the urinary tract and/or vagina. Studies of the healthy (asymptomatic) bladder microbiome have shown that it is frequently predominated by lactobacilli [2].…”
Section: Introductionmentioning
confidence: 99%
“…L. iners, L. gasseri, and L. jensenii have frequently been observed within the urinary microbiome of females with incontinence [2,3,18]. Nevertheless, L. gasseri and L. jensenii have been found to be effective in inhibiting the growth of several urogenital pathogens [11,19].…”
Section: Introductionmentioning
confidence: 99%